Hybrid Storage Architecture for Internet of Things - C. Junior, Braulio L. D.; de Macedo, Douglas D. J.; Moreno, Edward David; Dantas, Mario A. R. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2018: Anais do XIX Simpósio em Sistemas Computacionais de Alto Desempenho, 2018)
Internet of Things (IoT) is part of our life. Some studies predict a considerable increase of up to 5 times on the number of connected devices by 2020. A significant challenge is how to manage this amount of data generated. In this paper, a hybrid storage architecture for IoT is proposed. The most used NoSQL databases types and two essential types of data of IoT sensors were selected. The results suggest that architecture is a feasible approach to address the ever-growing amount of data generated in IoT. Additionally, after an architecture evaluation, the results have shown that Redis achieved better overall performance.